A Numerical Procedure to Evaluate Memory Effects in Non‐Equilibrium Coarse‐Grained Models. Issue 4 (3rd November 2020) - Meyer, Hugues; Wolf, Steffen; Stock, Gerhard; Schilling, Tanja
Abstract: When developing coarse‐grained models of complex processes out of equilibrium, one encounters the non‐stationary generalized Langevin equation. The most important feature of this equation is the presence of a non‐stationary memory kernel. Here, a method is presented to infer this memory kernel from MD simulation data in non‐equilibrium processes. The method provides an improvement of a previously published numerical scheme, the applicability of which is limited by a truncation problem. As an illustration, the method is applied to ion dissociation of NaCl in water, for which non‐trivial dampened oscillations are observed in the memory kernel. Abstract : A numerical method is presented to analyze reaction coordinates from simulation data in terms of memory effects. The method allows to efficiently construct non‐stationary memory kernels. It is tested with the example of NaCl dissociation in water.